(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the efficacy of silicon intubation vs dacryocystorhinostomy in treating nasolacrimal duct blockage Study Design: A Randomized Controlled Trial Study Place and Duration of Study: This study was conducted at the Department of Clinical Ophthalmology, Khyber Girls's medical College, Hayatabad Medical Complex (HMC), Peshawar from 09th October 2022 to 9th April 2023. Methods: 446 individuals with nasolacrimal duct obstruction (NLDO) were included in the research. Every patient was divided into two groups. Dacryocystorhinostomy (DCR) with silicon intubation was performed on Group A, whereas DCR without intubation was performed on Group B. Results: The sample as a whole was 35.1 + 9.2 years old on average. Group A's mean age was 34.9 + 9.3 years, whereas Group B's mean age was 35.2 + 9.1 years (p 0.730). Males made up 61.9% of group A and 56.5% of group B, respectively (p 0.248). In group A, the mean duration of symptoms was 11 + 3.2 days, whereas in group B, it was 10.4 + 2.9 days (p 0.082). Upon follow-up, group A's effectiveness (measured by the total remission of symptoms) was 79.4%, whereas group B's was 69.5% (p 0.017). Conclusion: When compared to DCR without intubation, silicon intubation greatly increases the effectiveness of DCR in individuals with NLDO.